Angle of Attack Sensor for Small Fixed-Wing Unmanned Aerial Vehicles - Kriangkrai Wanngoen; Nanthawat Saetunand; Watcharapol Saengphet; Suradet Tantrairatn (Proceedings, 2020)
The angle of attack (AOA) is an important parameter for estimating aerodynamic parameter the performance and stability of aircraft. Currently, AOA sensors are used in general aircraft. However, there is no a reasonable-price AOA sensor that is compatible to a small fixed-wing unmanned aerial vehicles (UAVs). This research aims to designs and constructs angle of attract (AOA) sensor for small fixed-wing unmanned aircraft. Mechanism Design, which is similar to aerodynamic wheatear vane, can operate in airspeed 10−30 m/s. The direction of airfoil aligns with the air flow direction. When the AOA of the UAV changes, the air flow changes the direction, resulting in the change of airfoil direction. The high-resolution rotary encoder, that was used to measure the angle of the airfoil, was installed with the fin airfoil. For experiment, the accuracy of the AOA sensor was validated by comparing the angles obtained from the encoder with the standard rotary table in static and wind tunnel. Finally, the AOA sensor, which was attached on aircraft, was verified and recorded in flight test. As the results of the measurement, the airfoil angles detected by the encoder were in good agreement with the standard angles.